Exercise in the cold - Nimmo, M. (Journal of Sports Sciences, 2004)
Exercising in the cold is not an attractive option for many athletes; however, defining what represents cold is difficult and is not standard for all events. If the exercise is prolonged and undertaken at a moderate intensity, environmental temperatures around 11°C can be an advantage. If the intensity is lower than this value and the individual does not generate sufficient metabolic heat to offset the effects imposed by the cold environment, then temperatures of 11°C can be detrimental to performance. Similarly, when the performance involves dynamic explosive contractions, then a cold ambient temperature can have a negative influence. Additional factors such as the exercising medium, air or water, and the anthropometric characteristics of the athlete will also make a difference to the strategies that can be adopted to offset any negative impact of a cold environment on performance. To plan for a performance in the cold requires an understanding of the mechanisms underpinning the physiological response. This review attempts to outline these mechanisms and how they can be manipulated to optimize performance.